Dose Response of Hp(0.07) on TLD-700 and TLD-900 Based Ring Dosimeters to the Sr-90 Exposure - Jumpeno, E. B.; Anggraeni, R.; Putri, M. Muharani; Barokah, S. N.; Adisti, F. N. (Atom Indonesia, 2024)
The preparation of radiopharmaceuticals may necessitate close contact with the radioactive source. In this case, high-energy beta-emitting nuclides can cause a high exposure. There are two methods of measuring the dose in the extremities, including using a bracelet and a ring dosimeter. In this study, the response of Hp(0.07) dose in TLD-700 and TLD-900-based ring dosimeters to Sr-90 beta radiation will be compared for parameters of distance, time, and angle of irradiation. The dosimeters were irradiated using Sr-90 at a distance of 5, 7, and 10 cm from the source surface and all of them were subsequently read with TLD Reader. The same type of dosimeters were exposed to Sr-90 for 1 day, 2 days, and 3 days at a distance of 7 cm and read. At a distance of 7 cm, the other dosimeters were irradiated at angles of 30°, 60°, -30°, and -60°, and then read. The study shows that the relationship between the distance of irradiation to Hp(0.07) dose is polynomial with a correlation factor of 1, both for TLD-700 and TLD-900-based ring dosimeters. The dose response at the variation of irradiation time showed linear behavior with correlation coefficients of 0.9942 and 0.9999 for TLD-700 and TLD-900, respectively. The decrease in Hp(0.07) response in TLD-700 reached 14-31 % for the irradiation angle of ±30o and 23-27 % in TLD-900 for the same angle. Meanwhile, the decrease in Hp(0.07) response at the angle of irradiation ±60o reached 48 % for TLD-700 and 66-67 % for TLD-900.